Do dehydroepiandrosterone, progesterone, and testosterone influence women's depression and anxiety levels? Evidence from hair-based hormonal measures of 2105 rural Indian women. (November 2019) - Walther, A.; Tsao, C.; Pande, R.; Kirschbaum, C.; Field, E.; Berkman, L.
Highlights: In a sample of 2105 women from rural India, hair samples were obtained for steroid hormone quantification. Higher depressive burden is associated with lower levels of dehydroepiandrosterone. A positive association between testosterone and both depressive and anxiety symptoms emerges. The association between psychological distress and testosterone is sensitive to how non-detectable values are treated. Progesterone shows no clear association with either depressive or anxiety symptoms. Abstract: Depressive and anxiety disorders substantially contribute to the global burden of disease, particularly in poor countries. Higher prevalence rates for both disorders among women indicate sex hormones may be integrated in the pathophysiology of these disorders. The Kshetriya Gramin Financial Services study surveyed a random sample of 4160 households across 876 villages in rural Tamil Nadu, India. An interviewer-administered questionnaire was conducted to quantify depressive (K6-D) and anxiety (K6-A) symptoms. Alongside, hair samples for sex hormone profiling were collected from a subsample of 2105 women aged 18–85 years. Importantly, 5.9%, 14.8%, and 46.3% of samples contained non-detectable hormone levels for dehydroepiandrosterone, progesterone, and testosterone, respectively. Our primary analysis imputes values for the non-detectable sample and we check robustness of results when non-detectable values are dropped. In this cohort of women from rural India, higher depressive symptomatology is associated with lower levels of dehydroepiandrosterone and higher depressive and anxiety symptoms are associated with higher levels of testosterone. Progesterone shows no clear association with either depressive or anxiety symptoms. These results support a potential protective effect of higher endogenous dehydroepiandrosterone levels. An important caveat on the potential negative effect of hair testosterone levels on women's mental health is that the testosterone analysis is sensitive to how non-detectable values are treated.